Reviews of Books - W., E. J.; G., J. A. K.; H., J. P.; F., T. W. (Irish Geography, 2017)
MERSEYSIDE. A SCIENTIFIC SURVEY. Published for the British Association Liverpool Meeting. 1953, by the University of Liverpool Press. 299 pp. 2 pocket maps. 21s. MAPS AND THEIR MAKERS. An Introduction to the History of Cartography, by G. R. Crone. Hutchinson, London, 1953. 181 pp. 71 / 8 in. x 4#fr1/2> in. 8s. 6d. THE SKIN OF THE EARTH, by A. Austin Miller. Methuen, London, 1954. 198 pp., 67 illustrations. 21s. THE EAST MIDLAND GEOGRAPHER, No. 1, June, 1954.